Elementary school learning system in Trenggalek during the covid 19 pandemic - Nur Rahmadani, Dhenisa; Eka Rahayu, Putri; Damariswara, Rian (Universitas Nusantara PGRI Kediri, 2022)
This article is based on finding out systematic learning in elementary school during the COVID-19 pandemic in the Trenggalek area. The main target points are teachers, guardians, and elementary students regarding the process of teaching and learning activities during the covid-19 pandemic. The method used in this study is a qualitative method, namely the method used by asking for some information from several parties concerned directly in accordance with the facts. Giving various questions and statements to the person concerned to receive the answer (Sugiyono, 2014: 142). And the data collection method used is a questionnaire. The data analysis method uses the Miles & Hubberman (2014) model which includes data reduction, presentation, verification, and conclusions. This study uses interview techniques, so that valid data sources can be obtained. Checking the validity of the data using triangulation of sources, namely teachers, students, and guardians of students. This information was obtained not only from 1 or 2 sources, but from several elementary schools in rural and urban areas such as SDN 2 Margomulyo, SDN 1 Tasikmadu, SDN 2 Sawahan, SDN 1 Ngadisoko, and SDN 1 Trenggalek. The selection of resource persons must also be appropriate, who are good at conveying information which can be proven to be true, which is an important reference in the preparation of this article. The quality of the learning media used to complete important points in order to improve the quality of the article